Assessment of professional learning in supervised practicum: exploratory studyin early childhood education - Araújo, Sara Barros (2021)
This study aims to analyze professional learning assessment procedures considering the specific teaching performance profile in early childhood education. A cohort of Portuguese students involved in a practicum in early childhood education, at a master level, participated in this exploratory study. Data were collected using an assessment instrument composed of 25 dimensions organized in four domains (Observation, Planning, Action and Reflection), applied at two different instances: regulatory assessment and final assessment. The results showed a statistically significant and positive evolution in 21 of the 25 dimensions examined, between the two instances of assessment. Data allow conclusions to be drawn regarding the learning of professional skills, and the potentialities of an authentic and co-participative approach in the assessment of practical training and in the endogenous understanding of training processes.